Natural Product from the Deep Sea - Umezawa, Kazuo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
After the long history of screening, it is becoming difficult to find novel compounds from microorganisms and plants anywhere in the world. Until now, more than about 30,000 marine natural products have been reported. However, with the development of marine natural products research, the hit rate of new compounds is also decreasing. Scientists are now turning their attention to the deep sea, where a high hit rate of novel compounds is expected. Many small compounds and peptides from microorganisms and sponges are with therapeutic activity are shown in this book. This Special Issue Book, "Natural Products from the Deep Sea", should be useful for the screening of novel and useful compounds from nature.